Menggagas Birokrasi yang Transparan dalam Pelayanan Publik - Dedek Kusnadi (Fakultas Syariah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2011)
Public demand for more transparent public services increased along with governance reform, bureaucracy in the reformation era and the regional autonomy should realy emphasize the aspect of effeciecy, effectiveness, professialism, merit system, public servant. Trasparancy in the context of public service is an open, easy, and accessibl by all parties who need and available sufficiently and easy understood. Trasparancy bureaucracy in standart operation of public service is all the service activities undertaken by public service providers as an effort to fulfill the needs service recipients and implementation of legistation.